An efficient approximation of the supercell approach to the calculation of the full phonon spectrum. (March 2021) - Duong, Thien C.; Paulson, Noah H.; Stan, Marius; Chaudhuri, Santanu
Abstract: The supercell approach to first-principles calculations of an alloy's full phonon spectrum is computationally expensive. It is therefore rarely used for calculating temperature dependent free energies of alloy phases or for calculating alloy phase diagrams. Amid the wider acceptance of uncertainty evaluation and the use of more efficient methods for materials design, the supercell approach is revisited and a simpler and more computationally efficient approximation is proposed. The new method is then used to calculate the Cr-Ni temperature dependent thermodynamic properties and phase diagram, resulting in predictions that are in good agreement with previous thermodynamic assessment. The new approach can facilitate accurate and rapid CALPHAD thermodynamic assessments of multi-component systems.